The Influence of Kopiko Product Advertisement on the Enhancement of Brand Awareness - Maya Desvita Sari (Asosiasi Ahli Administrasi Indonesia, 2022)
This research aims to investigate The Influence of Kopiko Product Advertisement on the Enhancement of Brand Awareness in the Korean Drama